Arthroscopic debridement versus refixation of the acetabular labrum associated with femoroacetabular impingement: Updated mean 7 year follow-up. Issue 7 (29th July 2019) - Larson, Christopher M.; Giveans, M. Russell; McGaver, Rebecca Stone; Weed, Katelyn N.
Objectives: The acetabular labrum provides sealing function and a degree of hip joint stability. Previous early (16 month) and mid-term (mean 3.5 years) follow-up of this cohort reported better patient related outcome measures in the refixation group. To update the results of labral refixation versus focal labral excision/debridement in a cohort of patients who underwent arthroscopic correction of femoroacetabular impingement (FAI). Methods: We reported patients who underwent labral debridement/focal labral excision during a period before the development of labral repair techniques. Patients with labral tears thought to be repairable with our current arthroscopic technique were compared with patients who underwent labral refixation. In 46 hips, the labrum was focally excised/debrided (group 1); in 54 hips, the labrum was refixed (group 2). Outcomes were measured with modified-Harris-Hip-Score (mHHS), Short Form-12 (SF-12), and a visual-analog-scale (VAS) for pain preoperatively and postoperatively. Results: Mean age was 33 years in group 1 and 28 years in group 2 with mean follow-up of 7 years (range, 2-13.6 years). At mean follow-up, subjective outcomes were significantly improved (P<.01) for both groups compared with preoperative scores. The mHHS (P=.004), SF-12 (P=.016), and VAS pain scores (P<.001) were all significantly better for refixation group compared with debridement group. Although most recent outcomes for both groups fell at mean 7 years' follow-up in comparison to 16 month and 3.5 year follow-up, the disparity between groups was greater in favor of labral refixation. Good-to-excellent results were 47.7% in debridement and 82.4% in refixation (p<.001), and failure rates were 31.8% (debridement) and 13.7% (refixation group) (p =.034). There were 4 revisions in the debridement group and none in the refixation group. Conclusion: Longer term follow-up comparing focal labral debridement/excision to refixation revealed a decrease in patient related outcome scoring and good/excellent results in both groups. Ultimately, there was a greater drop in outcome measures and good/excellent results in the debridement group and better maintenance of results in the refixation group at mean 7 years follow-up.